2004
DOI: 10.2134/jeq2004.1033
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preferential Flow at Varying Irrigation Rates by Quantifying Mass Fluxes

Abstract: Solute concentration and soluble dye studies inferring that preferential flow accelerates field-scale contaminant transport are common but flux measurements quantifying its impact are essentially nonexistent. A tile-drain facility was used to determine the influence of matrix and preferential flow processes on the flux of mobile tracers subjected to different irrigation regimes (4.4 and 0.89 mm h(-1)) in a silt loam soil. After tile outflow reached steady state either bromide (Br; 280 kg ha(-1)) or pentafluoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 25 publications
(30 reference statements)
0
38
0
Order By: Relevance
“…That means that the artificial drainage response for heavy rainfall events is also quick if the soil moisture is low. This may again indicate that high rainfall intensities accelerate water fluxes through preferential flow pathways (GISH et al, 2004). Also KUNG et al (2000) reported that 90% of the tracers were found during the first day in a leaching experiment in Indiana (USA).…”
Section: Lag Time and Time Of Peak Artificial Drainage Response Aftermentioning
confidence: 94%
“…That means that the artificial drainage response for heavy rainfall events is also quick if the soil moisture is low. This may again indicate that high rainfall intensities accelerate water fluxes through preferential flow pathways (GISH et al, 2004). Also KUNG et al (2000) reported that 90% of the tracers were found during the first day in a leaching experiment in Indiana (USA).…”
Section: Lag Time and Time Of Peak Artificial Drainage Response Aftermentioning
confidence: 94%
“…Most of these experiments monitored the drainage water discharge and measured tracer content in the drain flow (Bengtsson et al, 1992; Kung et al, 2000a, b;Gish et al, 2004;Petersen et al, 2004). Few studies combined the monitoring of drainage water discharge with the analysis of the tracer content in the soil water or the direct 7 observation in the solum in case of dye tracer experiments (Mériaux, 1973;Merot and Hamdi, 1991;Øygarden et al, 1997;Kohler et al, 2003;Shipitalo et al, 2004).…”
Section: Subsurface Water Pathways In Drained Soils As Determined In mentioning
confidence: 99%
“…After 2-6 weeks, blue dye was examined by excavating a trench and photographing the exposed soil surface. Gish et al (2004) used dye tracer to determine the relative importance of field scale matrix and preferential flow processes on transport of mobile chemicals under steady state infiltration. Akhtar et al (2003a) used dye tracer to visualize flow pattern for unsaturated conditions.…”
Section: Introductionmentioning
confidence: 99%